(untitled) (Revista Internacional de Formação de Professores, 2016)
This research addresses the challenges of the Faculty of Education of trainees in relation to the specific content domain of the disciplines of Basic Education - Early Years , during the course of the Supervised Internship activities. The methodology used in addition , the literature , was consolidated through participant observations , reports, written records and images. The interest in the area materialized when our exercise as teaching the curriculum component Supervised . This study received financial support from the Bahia State University and concluded that the difficulties encountered by trainees / teachers with regard to the content area is a result of the disconnection between the practical reality and the academic content of future teachers and the separation between the specific disciplines and pedagogical.